Transcriptomic and biochemical effects of pycnogenol in ameliorating heat stress-related oxidative alterations in rats. (October 2020) - Atta, Mustafa S.; Farrag, Foad A.; Almadaly, Essam A.; Ghoneim, Hanan A.; Hafez, Ahmed S.; Al Jaouni, Soad K.; Mousa, Shaker A.; El-Far, Ali H.
Abstract: Background: Heat stress is a condition that is due to extreme heat exposure. It occurs when the body cannot keep its temperature healthy in response to a hot climate and associated with oxidative stress. Testicular hyperthermia can induce apoptosis of sperm cells, affect sperm production and decrease sperm concentration, leading to sperm disorder, for this reason, we examined the protective impact of pycnogenol that it has a wide range of biological benefits, including antioxidant, anti-inflammatory and anti-cancer activities against the oxidative alterations that happen in testicular and brain tissues due to heat stress in rats. Study design: Forty-eight Wistar male rats, approximately around 6 weeks age were allocated randomly into four groups (12 in each) of control, HS (subjected to heat stress and supplemented orally with 50 mg of pycnogenol/kg b. w./day dissolved in saline for 21 days), and pycnogenol (rats supplemented orally with 50 mg of pycnogenol/kg b. w./day dissolved in saline for 21 days). Results: Data revealed a promising role of pycnogenol as an antioxidant, natural product to successfully reverse the heat-induced oxidative alterations in testicular and brain tissues of rats through significant upregulation of superoxide dismutase-2, catalase, reduced glutathione, and anti-apoptotic gene, while downregulating pro-apoptotic, and heat shock protein70. Pycnogenol treatment also reversed the reproductive hormone level and spermatogenesis to their normal values. Conclusion: Pycnogenol as a natural protective supplement could recover these heat stress-induced oxidative changes in testes and hypothalamus. Graphical abstract: Image 1 Highlights: Pycnogenol significantly improves of antioxidants related genes, and BCL2 gene. Pycnogenol is downregulating heat shock protein70 and Bax genes. Pycnogenol normalizes the reproductive hormone level and spermatogenesis. Pycnogenol reverses heat-induced damaged in rat testicular and brain tissues.